2001
DOI: 10.1542/peds.107.5.e67
|View full text |Cite
|
Sign up to set email alerts
|

Home and Videotape Intervention Delays Early Complementary Feeding Among Adolescent Mothers

Abstract: ABSTRACT. Background. The American Academy of Pediatrics, the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), and the World Health Organization recommend that infants receive only breast milk or formula for the first 4 to 6 months of life, followed by the introduction of complementary foods. Despite these recommendations, many infants, particularly those with adolescent mothers, receive solid foods (often cereal mixed with formula in a bottle) and liquids other than formula or br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 31 publications
(26 reference statements)
0
87
1
4
Order By: Relevance
“…25 We furthermore emphasized staff training and monitoring to ensure that staff acquired and used skills to teach, promote, and model positive parenting faithfully. 20 Similar to programs that specifi cally target teenage mothers, 15 our program signifi cantly infl uenced school reentry and graduation. This effect may have been due to the home visitors' consistent messages and case management activities delivered in the context of their ongoing relationship with the teen.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…25 We furthermore emphasized staff training and monitoring to ensure that staff acquired and used skills to teach, promote, and model positive parenting faithfully. 20 Similar to programs that specifi cally target teenage mothers, 15 our program signifi cantly infl uenced school reentry and graduation. This effect may have been due to the home visitors' consistent messages and case management activities delivered in the context of their ongoing relationship with the teen.…”
Section: Discussionmentioning
confidence: 91%
“…The curricula were grounded in social cognitive theory and were developed by a child development psychologist and an anthropologist specifi cally for urban, African American adolescent mothers. 19,20 The parenting curriculum sessions aimed to improve teens' understanding of child development, teach and model good parenting attitudes and skills, and promote appropriate health care use. If the adolescent mother gave consent, the home visitor attempted to engage the baby's father along with the mother in parenting sessions.…”
mentioning
confidence: 99%
“…162 Grandmothers have also been found to have a strong influence on parents' feeding decisions for children in infancy and early childhood and potentially into late adolescence. [163][164][165] A study of low-income black mothers participating in the Special Supplemental Nutrition Program for Women, Infants, and Children showed that having a grandmother in the household was associated with lower food insecurity. 166 Despite these data, very few studies have examined grandparents as agents of change for grandchild obesity treatment.…”
Section: Research On Grandparents As Agents Of Changementioning
confidence: 99%
“…Thus, many of the interventions on breast-feeding (24)(25)(26) and early complementary feeding (27) have focused on providing education to increase knowledge among mothers and their social support providers (e.g. spouse, own mother, health professionals).…”
mentioning
confidence: 99%